Nonlinear fast kurtogram for the extraction of gear fault features with shock interference. (1st February 2023) - Ma, Hao; Wang, Jinrui; Han, Baokun; Bao, Huaiqian; Liu, Zongling; Jiang, Xingwang; Xing, Shuo
Abstract: The extraction of gearbox fault features under shock interference is an exceedingly difficult and valuable subject. The effective usage of the resonance frequency band is one of the solutions for this subject. However, the existing fast kurtogram (FK) method is prone to misdiagnosis due to the sensitivity of this method to aperiodic shocks. To overcome the sensitivity of the FK method to irrelevant shock, this paper proposes a nonlinear fast kurtogram (NFK) method. First, Z-score normalization is performed on the signal. Then, Sigmoid is used to improve the fault representation under shock interference. Third, the signal is divided into different frequency bands, and the band with the largest kurtosis is selected for filtering. Finally, the gear fault is analyzed by the square envelope spectrum. Simulation and experimental verification are used to demonstrate the effectiveness of the proposed method. The results show that gear fault features can be extracted under shock interference by the NFK method.